Guidance Document on the World Food Programme - Feinstein International Center (Tufts Archival Research Center, 2005)
This document has been prepared as part of the World Food Programme (WFP) Sudan's Food Aid Forum held from June 6-9 2006, in Khartoum, Sudan. The purpose of the document is threefold: 1. To inform those who did not attend the Forum on its content and outcome 2. To serve as an outcome document for those who did attend 3. To be a tool for WFP in their strategic planning process.